2019
DOI: 10.25077/jsfk.5.3.207-211.2018
|View full text |Cite
|
Sign up to set email alerts
|

Karakterisasi dan Uji Sitotoksik Daun Jeruju (Acanthus illicifolius)

Abstract: Tumbuhan Jeruju (Acanthus illicifolius) merupakan salah satu tumbuhan mangrove yang banyak ditemukan di daerah tepi pantai di Sumatera Barat. Masyarakat  di daerah Ketaping dan Pariaman Sumatera Barat mengkonsumsi buahnya untuk mengobati kanker. Penelitian ini bertujuan untuk  melakukan karakterisasi dan menentukan, aktivitas sitotoksik ekstrak etanol dan fraksi jeruju (Acanthus illicifolius) dengan metode Brine Shrimp Lethality Test (BSLT). Daun dimaserasi dengan etanol 70% selama 3 hari, kemudian difraksinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 6 publications
2
4
0
Order By: Relevance
“…The ethanol extract of yield of 19.6%, and n-hexane fraction of 4.3%. These results fraction yield a larger of previous research that is 2.2% 22 . The results of phytochemical screening on ethanol extracts contain flavonoid compounds with red due to colors, tannins (blue), terpenoids (green), alkaloids (orange to red), and steroids (yellow) (Tab 1, fig 1).…”
Section: Resultssupporting
confidence: 77%
“…The ethanol extract of yield of 19.6%, and n-hexane fraction of 4.3%. These results fraction yield a larger of previous research that is 2.2% 22 . The results of phytochemical screening on ethanol extracts contain flavonoid compounds with red due to colors, tannins (blue), terpenoids (green), alkaloids (orange to red), and steroids (yellow) (Tab 1, fig 1).…”
Section: Resultssupporting
confidence: 77%
“…In addition, jeruju leaf extract contains alkaloids compounds, flavonoids, polyphenols, phenyletanoid glycosides and coumarins. The methanol part of thistle leaf extract has a pharmacological effect to inhibit edema (inflammation) (Suryati et al, 2018).…”
Section: Plan Part (Leaf)mentioning
confidence: 99%
“…Mangroves have many benefits that are directly related to human life, ranging from ecological benefits to being a source of food and medicine. Many universities and research institutes have explored various plants as sources of medicine but have not looked at the benefits of mangroves (Suryati et al, 2018). Mangroves are a diverse group of salt-tolerant plants that grow in tropical and subtropical intertidal forests and represent a rich biodiversity of plants, animals and microorganisms (Cai et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, alternative treatment approaches to eliminate resistant tumor cells are needed (Zhang and Chen, 2018). Referring to the description of the explanation put forward by Suryati, et al (2018) explained that looking for sources of compounds found in plants can be used as another option in the process of curing cancer.…”
Section: Introductionmentioning
confidence: 99%